Atrocity archives eaudiobook - Stross, Charles (Laundry Files, 2010)
A Hugo Award winner and best-selling author, Charles Stross combines the best elements of science fiction and fantasy. In The Atrocity Archives, a lowly computer geek working for a secret British intelligence agency gets promoted to field service after accidentally saving lives in a disaster. Now he's faced with saving the universe using only his smarts and a disembodied hand that renders him invisible. Stross' award-winning novella, The Concrete Jungle, is also included.